Allostatic Load in Cancer: A Systematic Review and Mini Meta-Analysis. Issue 3 (July 2021) - Mathew, Asha; Doorenbos, Ardith Z.; Li, Hongjin; Jang, Min Kyeong; Park, Chang Gi; Bronas, Ulf G.
Background: Individuals with cancer experience stress throughout the cancer trajectory. Allostatic load (AL), a cumulative multi-system measure, may have a greater value in stress assessment and the associated biological burden than individual biomarkers. A better understanding of the use of AL and its operationalization in cancer could aid in early detection and prevention or alleviation of AL in this population. Purpose: To consolidate findings on the operationalization, antecedents, and outcomes of AL in cancer. Methods: Seven databases (CINAHL, Ovid MEDLINE, Web of Science, APA PsycInfo, Scopus, Embase, and Cochrane CENTRAL) were searched for articles published through April 2020. The NIH tools were used to assess study quality. Results: Twelve studies met inclusion criteria for this review. Although variability existed in the estimation of AL, biomarkers of cardiovascular, metabolic, and immune systems were mostly used. Associations of AL with cancer-specific variables were examined mostly utilizing population-databases. Significant associations of AL with variables such as cancer-related stress, positive cancer history, post traumatic growth, resilience, tumor pathology, and cancer-specific mortality were found. Mini meta-analysis found that a one-unit increase in AL was associated with a 9% increased risk of cancer-specific mortality. Conclusion: This review reveals heterogeneity in operationalization of AL in cancer research and lack of clarity regarding causal direction between AL and cancer. Nevertheless, AL holds a significant promise in cancer research and practice. AL could be included as a screening tool for high-risk individuals or a health outcome in cancer. Optimal standardized approaches to measure AL would improve its clinical utility.